2017
DOI: 10.1038/srep46426
|View full text |Cite
|
Sign up to set email alerts
|

A Formulated TLR7/8 Agonist is a Flexible, Highly Potent and Effective Adjuvant for Pandemic Influenza Vaccines

Abstract: Since 1997, highly pathogenic avian influenza viruses of the H5N1 subtype have been transmitted from avian hosts to humans. The severity of H5N1 infection in humans, as well as the sporadic nature of H5N1 outbreaks, both geographically and temporally, make generation of an effective vaccine a global public health priority. An effective H5N1 vaccine must ultimately provide protection against viruses from diverse clades. Toll-like receptor (TLR) agonist adjuvant formulations have a demonstrated ability to broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 63 publications
(72 reference statements)
2
57
0
Order By: Relevance
“…The strong adjuvanticity of 3M‐052 exhibited in our study was also observed in other reports in which 3M‐052 was formulated into vaccines using lipid‐based or combined lipid‐Alhydrogel® delivery platforms. Fox et al reported that a liposome‐Alhydrogel® formulation with 3M‐052 enhanced the antigen‐specific IgG1 and IgG2c titers and frequency of T H 1 cytokine‐producing CD4 + memory cells of a tuberculosis vaccine in mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The strong adjuvanticity of 3M‐052 exhibited in our study was also observed in other reports in which 3M‐052 was formulated into vaccines using lipid‐based or combined lipid‐Alhydrogel® delivery platforms. Fox et al reported that a liposome‐Alhydrogel® formulation with 3M‐052 enhanced the antigen‐specific IgG1 and IgG2c titers and frequency of T H 1 cytokine‐producing CD4 + memory cells of a tuberculosis vaccine in mice.…”
Section: Discussionsupporting
confidence: 88%
“…To address this limitation, the lipophilic derivative 3M‐052 was developed as a next‐generation TLR7/8 agonist that is retained at the injection site longer . Because of the lipophilic nature of 3M‐052, liposomes or other lipid‐based delivery vehicles have been used for subcutaneous, intramuscular, or intratumoral injections of 3M‐052 …”
Section: Introductionmentioning
confidence: 99%
“…This combination allows tumor suppression in CT26 colon cancer bearing mice and establishment of long-term immunity [239]. In 2017, Hoeven et al described 3M-052 formulation development studies [240]. The hydrophobicity of 3M À 052 allows its incorporation in lipid-based formulations (anionic, cationic, PEGylated or neutral liposomes or oil-in-water emulsion), which were able to protect both mice and ferrets from infections caused by lethal H5N1 homologous virus.…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%
“…The effects of vita‐PAMPs as signature of microbial viability in live vaccination can be substituted by synthetic TLR8 agonists, such as CL075, which could overcome the safety concerns of live vaccines . The efficacy of TLR7/8 ligands as potent adjuvants was already confirmed in different experimental setups including nonhuman primates . Interestingly, the archaeon M. stadtmanae is recognized by the innate immune system solely dependent on TLR8 and TLR7 and apparently without the involvement of any other innate immune receptors .…”
Section: Role Of Microbial Rna In Vaccine Developmentmentioning
confidence: 99%